Заметки о семейном праве Ларсы (Старовавилонский период - Яковсон, В.A. (2012)
Jakobson, Vladimir А., Notes on Family Law in Larsam (Old Babylonian Period); English summary р.231; ad YOS VIII 154, 141, 149, 152, 120, 118